From diaspora community to diaspora literature: the case of Vietnamese boat people in Germany. Issue 2 (3rd July 2018) - Tinh Vy, Tran
ABSTRACT: The formation of Vietnamese community in Germany was determined by both historical events in Vietnam and turbulent socio-political context in Germany. The boat people, who were referred in German as Bootsflüchtlinge (boat people) or Kontingentflüchtlinge (contingent refugees), have been rescued by the ship Cap Anamur from 1979 onwards and enjoyed social support for their integration. In contrast, the contract workers experiencing harsh time after the reunification of East and West Germany in 1990 were stigmatized as bad immigrants in mainstream media and society. Within such a framework, I will tell two opposite stories of the formation and the development of the two main Vietnamese communities in Germany. The distinguished groups of Vietnamese also determine the essence of its diaspora literature which is not unified and fixed but diversified and fragmentary. In the second section, I focus more on the diasporic features of the literature by viewing how writers create their literary platforms to share their own memory and identity. The first representation is the establishment of Vietnamese Writers Abroad, based in the United States, which leads to the participation of Vietnamese boat people in Germany. This act is seen as the authors' effort to create a connecting community of those who shared the same collective memory towards homeland and host land. Not only participating in a literary association overseas, Vietnamese refugees in Germany have Viên Giác as their own socio-cultural centre. Interestingly, the formation, operation and transformation from Buddhism to non-Buddhism of the centre reflect political tendency in creating a forum by and for the refugees, who are mostly against the current regime in Vietnam. The network of authors and readers by Viên Giác centre shows the second representation of the Vietnamese refugees in Germany as the diaspora community that they all share religious and political interests.